Communication of sex, sexuality and erotism in Lambayeque” - Alarcón Llontop, Luis Rolando (2018)
Talking about sex, sexuality and erotism is natural but how it expresses can change depending in the audience and the context. Along with a quantitative methodology we looked for the connection between these three topics in a specific regional population: Chiclayo, Ferreñafe and Lambayeque. We worked with a sample of 597 people to whom we applied a survey of 17 questions, there were three variables, information, media content and sex evaluation, sexuality and erotism. We found that the place where the locals get more information about these topics are their education centers at 35.7%, at home 22.4%, the person they prefer to talk about sex, sexuality and erotism is their partner at 39,7% and very close their friends at 34.4%, and the subjects they prefer to talk about are pregnancy and contraceptives, sexually transmitted diseases and sexual activity according to 71.7%, 69.8% and 41.3% of the answers.